If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-(x+9)=-3(x-5)
We move all terms to the left:
4-(x+9)-(-3(x-5))=0
We get rid of parentheses
-x-(-3(x-5))-9+4=0
We calculate terms in parentheses: -(-3(x-5)), so:We add all the numbers together, and all the variables
-3(x-5)
We multiply parentheses
-3x+15
Back to the equation:
-(-3x+15)
-1x-(-3x+15)-5=0
We get rid of parentheses
-1x+3x-15-5=0
We add all the numbers together, and all the variables
2x-20=0
We move all terms containing x to the left, all other terms to the right
2x=20
x=20/2
x=10
| w-3.6=8.66 | | 1/2(x-160=5+7x | | x+2.4=9.15 | | 7h=-20+8h | | 10(x-8)=14 | | 16-1/5(x+10)=9 | | -18-13f=2-12f | | 5r^2-28r+15=0 | | 19=3x-11 | | 19+3x=4(-x+3)-49 | | −8.5x+0.54=−2.86 | | 8(10n-4)=6+80n | | 4v+14=82 | | 5(x+8)=8(X-1) | | -2m=10−7m | | -3c÷8=6 | | 14-m=9m-12m-16 | | -7v+3(v+3)=-11 | | 8x-32=4x-64 | | -7v+3(3+v)=-11 | | 15b=-17-2b | | 74-1,4t=62-0,2 | | 0.25=(x5) | | 17y=40+9y | | 8x-32=4x-32 | | -7b+10=-10-4b-10 | | (3-10w)+8w=18-3(w-5) | | 14=-5w+3(w+2) | | 2(d+10)=5(d+8)-2 | | 3u-10=-6u+8 | | 4÷3w-12=2÷3w | | 5q=-5+4q |